Về một bài toán biểu diễn tri thức tự nhiên - Vân, Phan Chí (Journal of Computer Science and Cybernetics, 2016)
In this paper author exposes one  concrete example on natural knowledge representation for illustration of the practice meanings of the concept on symmetric logical model and of their system on characteristic regions.